Diálogos entre processo civil e tecnologias emergentes: impactos metodológicos a partir de análises pragmáticas - Senna, João Marcos de Almeida (2021)
The present work aims to analyze to what extent the phenomenon of technological change in the due process of law impacts on the general theory of the process, particularly in the discussion about its current methodological stage, considering the doctrinal divergence between instrumentalism, formalism-evaluative, neoconcretism and pragmatism. It starts with an initial theoretical framework about which are the emerging technologies that make up this phenomenon and in what terms there is an integration of legal and algorithmic logics as a background, to later addresses regulatory aspects and some practical examples of these impacts in established principles, dogmas and institutes. It seeks to trace the contours of the current methodological crisis, mainly due to the partial dysfunctionality of the Justice system, the hypertrophy of the legislative functions of the National Council of Justice and the challenges of adapting the Judiciary to the digital transformation of society and the economy, strongly catalyzed by mobility restrictions imposed by the Covid-19 pandemic in 2020. At the end, the existence of a methodological pluralism is defended, which is revealed by several normative, doctrinal, philosophical and ideological aspects, but concludes by the approximation of the phenomenon of technological change with pragmatism